2017
DOI: 10.1111/rec.12494
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in an invasive rodent community favoring Black rats (Rattus rattus) following restoration of native forest

Abstract: One potential, unintended ecological consequence accompanying forest restoration is a shift in invasive animal populations, potentially impacting conservation targets. Eighteen years after initial restoration (ungulate exclusion, invasive plant control, and out planting native species) at a 4 ha site on Maui, Hawai'i, we compared invasive rodent communities in a restored native dry forest and adjacent non-native grassland. Quarterly for 1 year, we trapped rodents on three replicate transects (107 rodent traps)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…Therefore, rats and mice may be more likely to compete for habitat in the kīpuka themselves (Caut et al 2007). By contrast, in a recent study on the neighbouring island of Maui, Shiels et al (2017) observed that black rats dominated a restored native dry forest, while house mice prevailed over rats in the adjacent grassland. Thus, management strategies aimed at removing all invasive rodents may need to incorporate multiple methods to control both rat and mice populations.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, rats and mice may be more likely to compete for habitat in the kīpuka themselves (Caut et al 2007). By contrast, in a recent study on the neighbouring island of Maui, Shiels et al (2017) observed that black rats dominated a restored native dry forest, while house mice prevailed over rats in the adjacent grassland. Thus, management strategies aimed at removing all invasive rodents may need to incorporate multiple methods to control both rat and mice populations.…”
Section: Discussionmentioning
confidence: 90%
“…Our study stresses the importance of further investigations on vector-borne and zoonotic diseases on islands. For example, some common commensal species (e.g., R. tanezumi and Rattus rattus) can not only adapt to diverse environments (71)(72)(73) but also host a variety of zoonotic diseases (8,71). They are also regular invaders on islands (4).…”
Section: Discussionmentioning
confidence: 99%
“…Our study stresses the importance of further investigation on vector-borne and zoonotic diseases on islands. For example, some common commensal species, such as R. tanezumi and Rattus rattus, can not only adapt to diverse environments (Chaisiri et al, 2015;Shiels et al, 2017;Wilson et al, 2017) but also host a variety of zoonotic diseases (Chaisiri et al, 2015;Kosoy et al, 2015). They are also regular invaders on islands (Johnson and Stattersfield, 1990).…”
Section: Discussionmentioning
confidence: 99%